========================================================
Explanation:
Plug in x = -1 to find that
f(x) = 2|x-1|
f(-1) = 2|-1-1|
f(-1) = 2|-2|
f(-1) = 2*(2)
f(-1) = 4
If you repeat for x = 1, you should find that f(1) = 0
--------
Now use the average rate of change formula below. Effectively, we're using the slope formula more or less.
[tex]m = \frac{f(b)-f(a)}{b-a}\\\\m = \frac{f(1)-f(-1)}{1-(-1)}\\\\m = \frac{0-4}{1+1}\\\\m = \frac{-4}{2}\\\\m = -2\\\\[/tex]
The average rate of change on this interval is -2
This is the same as finding the slope through the points (-1, 4) and (1, 0).